Sosialisasi Landskap Linguistik Dalam Meningkatkan Soft Skills Mahasiswa - Dewi Nurmala; Diana Sopha; Zuindra Zuindra; Wais Al Qorni (LPPI UMN AL WASHLIYAH, 2024)
This article is the result of the hard work of a group of lecturers and students from the English literature study program at Al Washliyah Muslim Nusantara University and Harapan University in Medan. The goal of this community service is to find solutions to improve students' soft skills by introducing them to the linguistic landscape. The study of language use in public spaces is known as linguistic landscape. Signs on the road or notices about rules or prohibitions in specific places or areas become a linguistic landscape study. This service location was chosen based on the findings of an analysis of students at Harapan University, Medan's Faculty of Language and Communication via interview data with one of the lecturers. Based on the interview results, community service was performed at Harapan University in Medan. This activity improves students' soft skills by utilizing counseling and outreach methods regarding the linguistic landscape. The benefit of this counseling is that it helps students understand how the linguistic landscape can influence their attitudes and speech in social interactions, particularly on campus. Location surveys, obtaining permits, preparing materials, and community service training are all stages of activity. It is hoped that by participating in this activity, students at Harapan University's Faculty of Language and Communication in Medan will gain more knowledge and insight.